Content and Community Redux: Instructor and Student Interpretations of Online Communication in a Graduate Seminar - Mary E. Dykes; Richard A. Schwier (The Canadian Network for Innovation in Education (CNIE), 2003)
The experiences of an instructor and teaching assistant who employed online communication strategies in a graduate seminar are examined in this paper. This paper expands on the findings reported in an earlier article on virtual learning communities founded on social constructivist pedagogy (Schwier & Balbar, 2002). We examine how the instructors constructed and refined structured discussions of content with synchronous and asynchronous communication at the graduate level. The instructors offer several observations and principles that are organized into categories that illustrate the source, message, channel and receiver in the communication system. The critical reflections of the instructors are compared with data from interviews with students about learning experienced in the online discussions (Dykes, 2003). Findings include the realization that instructors may fundamentally misinterpret or overlook important elements of communication, but that students are robust learners who can transcend the limitations of the medium and the instructor if given the authority in a social constructivist learning environment.